ANALYSIS OF PREVENTIVE MAINTENANCE 110 VDC SYSTEM AT PLTM GUNUNG WUGUL PT. PLN INDONESIA POWER MRICA PGU - Safi'i, Ahmad; Mubarok, Rizky; Prasetyono, Rizki; Nasrulloh; Fachruroji; Adzin Murdiantoro, Randi (Journal of Electronic and Electrical Power Applications, 2023)
The battery is a back-up for the DC electrical system which is closely related to the protection system in a generator, so to find out the routine maintenance system of the 110 VDC battery system used at the Mount Wugul PLTM. This maintenance will measure the voltage and quality of the battery water in the battery. The aim of the research is to test the 110 VDC battery for daily maintenance, a visual inspection is carried out to ensure the physical condition of the battery is in good condition, to ensure the 110V DC battery remains in a stable condition and is ready to supply DC power to auxiliary equipment when an emergency occurs. From the test results, it was found that the voltage drop in cells number 1 and 7 was recorded at 0.3661 VDC and 1.1948 VDC respectively. It was necessary to take corrective action or replace the battery cells. By measuring the specific gravity of each battery cell, the average value of the specific gravity of the battery was 1,214.59, which is included in the recharge category, meaning that the battery needs to be re-charged. So the results of measuring these two voltages show that the respective voltage balance between positive to ground and negative to ground is in accordance with standards